Screening for candidate genes involved in the production of mouse subventricular zone proliferative cells and an estimation of their changes in evolutionary pressure during primate evolution - Tabata, Hidenori; Hachiya, Tsuyoshi; Nagata, Koh-ichi; Sakakibara, Yasubumi; Nakajima, Kazunori (Frontiers in Neuroanatomy, 2013)
During neocortical development, excitatory neurons are produced from apical progenitors in the ventricular zone (VZ) or from dividing cells in the subventricular zone (SVZ). We previously reported that the direct progenies of VZ cells in mice slowly exit the VZ and accumulate just above the VZ (lower SVZ) as multipolar migrating neurons, whereas subsequently dividing cells in the SVZ exit the VZ earlier than the former and become widely distributed in the SVZ. These two populations are named the slowly exiting population (SEP) and the rapidly exiting population (REP), respectively. In mice, REP cells include basal progenitors as the major population and are characterized by a long ascending process; their morphology resembles that of basal radial glial cells (bRGs), which have been observed in the inner and outer SVZ in primates. The dramatic increase in the number of bRGs in primates, especially in humans, is thought to underlie the acquisition of a huge cortex during evolution. We previously reported that the REP/SEP production rate in the lateral cortical VZ is higher than that in the dorsomedial VZ in mice. To search for molecules responsible for the higher REP production in the lateral cortical VZ, we conducted microarray analyses and identified genes that were differentially expressed between the lateral and medial VZs in mice. These genes were considered to be among the candidates responsible for the regulation of the REP/SEP production rate. To investigate the selection pressures during primate evolution on these candidate genes, we estimated the synonymous versus non-synonymous base substitution rates. As a result, the negative selection pressures on the Megf11, Dmrt3, and Cntn3 genes were found to be significantly weaker in primates than in non-primates, while those on Jag1, Ntrk2, and Pmp22 were stronger. Candidate molecules responsible for primate cortical expansion through an increase in bRGs may be included among these genes.